(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
“Life on the Mississippi” by Mark Twain is a semi-autobiographical work that blends memoir, history, and travel narrative. It explores the author’s experiences as a riverboat pilot and captures the cultural and economic significance of the Mississippi River during the 19th century. Twain’s vivid storytelling reflects the complexities of pre-Civil War America and industrial change. This paper examines the book’s historical value, themes, and literary style, providing an in-depth analysis of its portrayal of the Mississippi River as a symbol of transformation.